Study of Flow Simulation of Recirculation Zone of an V-Gutter - R. Anand; D. Lokesharun; V. Babu; A. C. Ramkumar (Research and Developments in Engineering Research Vol. 6, 2023)
The Afterburner is an additional combustion component used on some Jet engines, mostly those on military supersonic aircraft. Its purpose is to increase thrust, usually for a supersonic flight, take off and during combat. The afterburning process injects additional fuel into a combustor in the jet pipe behind the turbine, reheating the exhaust gas. Afterburner significantly increases thrust as an alternative to using a bigger engine with its weight penalty, but at the cost of increased fuel consumption (decreased fuel efficiency) which limits its use for short periods. The V-gutter is a flame stabilizing device used in Afterburners. The flow around the V-Gutter is highly complex due to the recirculating nature of the flow. The flame stabilization is characterized by the length of the recirculation zone hence the determination of recirculation is the objective of our study. Since the flow around the gutter is associated with flow separation and recirculation it is sensitive to probe interference and experimentation is costlier hence, we resort to Flow simulation using Ansys. The analysis of flow around V-Gutter and subsequent determination of recirculation zone is carried out with the help of the CFD Software Ansys Fluent. This aims to study the mass flow rate increases in the recirculation zone in which angles, according to the analysis of the three angles 30°, 45°, and 60°, respectively.